Demographics, Old-Age Transfers and the Current Account - Dao, Mai Chi.; Jones, Callum (Washington, D.C. : International Monetary Fund, 2018)
Building on the evolving literature on the topic, this paper reviews the relationship between demographics and long-run capital flows in both theory and in the data. For this purpose, we develop a two region overlapping generations model where countries differ in their population growth and mortality risk. Besides exploring the implications of demographics for saving and the current account over the long-run, we also study how these might be affected by differences in the coverage and sustainability of old-age transfer schemes. The model predicts that population structure and life expectancy (which affects the need to save to meet old age consumption) affect current account levels, and that while countries with more generous unfunded transfer schemes tend to have lower saving and more capital inflows over the long-run, this effect may be dampened by natural limits (on taxation) of these schemes. The key predictions of the model are generally supported by a rich panel dataset.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet